THEORETICAL AND METHODOLOGICAL FOUNDATIONS OF PLANNING AND BUDGETING ENTERPRISE ACTIVITIES IN MANAGEMENT ACCOUNTING - Abdumalik Abdiraximovich Tulyaganov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
This article comprehensively examines the theoretical and methodological foundations of planning and budgeting within the management accounting system of an enterprise. The study analyzes strategic and operational levels of planning, explores the economic essence of budgeting models, and highlights their integration with strategic management. Particular attention is paid to cost classification, variance analysis, risk assessment, and the impact of digital technologies on the budgeting process. The findings demonstrate that integrating management accounting with strategic management enhances financial stability and ensures efficient resource allocation within enterprises.